The Contribution of Emphaty to Prosocial Behavior in Student Teaching Volunteers - Khoirunnisa Virgiana Khan; Nurul Qomariyah (Lafadz Jaya Publisher, 2023)
Students are required to implement their knowledge to the community, one of which is by becoming a teaching volunteer. Teaching activities carried out by students are a form of prosocial behavior. Prosocial behavior can be influenced by internal factors, one of which is empathy. The purpose of this study is to test empirically the contribution of empathy to prosocial behavior in students who become teaching volunteers. The sampling technique used in this study is non-probability sampling with purposive sampling technique. This study was conducted on 108 respondents with certain criteria, that is active students who became teaching volunteers for at least 1 month. Data collected by distributing questionnaires containing the respondents' identities and the research scale. The scale used in this study is a helping attitude scale and an empathy scale. The data analysis technique used to test the hypothesis in this research is a simple linear regression test. Based on the results of data analysis, the F value was 31.114; R square of 0.227 and a significance value of 0.000 (p <0.01). This shows that there is a very significant contribution from empathy to prosocial behavior in students who become teaching volunteers and empathy contributes to prosocial behavior by 22.7%, while the remaining 77.3% is influenced by other factors outside of research.